Evaluation of Two Library-Independent Microbial Source Tracking Methods To Identify Sources of Fecal Contamination in French Estuaries - Gourmelon, Michèle; Caprais, Marie Paule; Ségura, Raphaël; Le Mennec, Cécile; Lozach, Solen; Piriou, Jean Yves; Rincé, Alain (Applied and Environmental Microbiology, 2007)
In order to identify the origin of the fecal contamination observed in French estuaries, two library-independent microbial source tracking (MST) methods were selected: (i) Bacteroidales host-specific 16S rRNA gene markers and (ii) F-specific RNA bacteriophage genotyping. The specificity of the Bacteroidales markers was evaluated on human and animal (bovine, pig, sheep, and bird) feces. Two human-specific markers (HF183 and HF134), one ruminant-specific marker (CF193'), and one pig-specific marker (PF163) showed a high level of specificity (>90%). However, the data suggest that the proposed ruminant-specific CF128 marker would be better described as an animal marker, as it was observed in all bovine and sheep feces and 96% of pig feces. F RNA bacteriophages were detected in only 21% of individual fecal samples tested, in 60% of pig slurries, but in all sewage samples. Most detected F RNA bacteriophages were from genotypes II and III in sewage samples and from genotypes I and IV in bovine, pig, and bird feces and from pig slurries. Both MST methods were applied to 28 water samples collected from three watersheds at different times. Classification of water samples as subject to human, animal, or mixed fecal contamination was more frequent when using Bacteroidales markers (82.1% of water samples) than by bacteriophage genotyping (50%). The ability to classify a water sample increased with increasing Escherichia coli or enterococcus concentration. For the samples that could be classified by bacteriophage genotyping, 78% agreed with the classification obtained from Bacteroidales markers.